Wilson’s disease: a rare rapidly progressive presentation with atypical imaging finding - Yahya, Arshad; Shamim, Robina (International Journal of Research in Medical Sciences, 2019)
Wilson’s disease is an autosomal recessive inborn error of copper metabolism characterized by inability of the liver to excrete copper into the bile, with excessive deposition of copper primarily in the liver and in the brain. To report a very rare acute presentation with rapidly progressive disease with some atypical imaging finding. Wilson’s disease was diagnosed on the basis of typical clinical picture, laboratory biochemical analysis and typical imaging finding. Apart from typical findings there were some atypical and rare findings which is the purpose of reporting these are a) very rare acute presentation and very rapid progression. b) Atypical Cerebral cortical enhancing lesion in both magnetic resonance imaging and computerized tomography scan with hyperintensity in diffusion weighted imaging in the corresponding areas. Aggressive presentation might be due to rapid accumulation of copper in the brain leading to cytotoxic edema in the accumulated area.